2010
DOI: 10.1186/1471-2458-10-494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and barriers to HIV testing among mothers at a tertiary care hospital in Phnom Penh, Cambodia. Barriers to HIV testing in Phnom Penh, Cambodia

Abstract: BackgroundOne-third of all new HIV infections in Cambodia are estimated to be due to mother-to-child transmission. Although the Ministry of Health adopted a policy of provider-initiated HIV testing and counseling (PITC), nearly a quarter of pregnant mothers were not tested in 2007. Greater acceptance of HIV testing is a challenge despite Cambodia's adoption of the PITC policy.MethodsA hospital-based quantitative and cross-sectional survey was conducted to assess the prevalence of and barriers to HIV testing am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
(13 reference statements)
2
21
1
Order By: Relevance
“…In current study having adequate knowledge about MTCT would enhance utilization of VHCT by about 10.6 times and this finding was in agreement with prior studies [11,15,24,25,31]. A study in East Ethiopia at Dire Dawa showed as mothers having good knowledge on VHCT were 15.6 times more likely to be tested (AOR 95% CI: 15.6 (13, 66.2) [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In current study having adequate knowledge about MTCT would enhance utilization of VHCT by about 10.6 times and this finding was in agreement with prior studies [11,15,24,25,31]. A study in East Ethiopia at Dire Dawa showed as mothers having good knowledge on VHCT were 15.6 times more likely to be tested (AOR 95% CI: 15.6 (13, 66.2) [25].…”
Section: Discussionsupporting
confidence: 91%
“…In this study about three quarter (76.2%) pregnant mothers underwent HIV testing on current pregnancy and this finding was in in line with a study in Ghana (76%) [14], Cambodia (76%) [15] and it was lower than the studies conducted in Northwestern Ethiopia at Gondar town (82.5%) [10], in a capital city of Ethiopia, Addis Ababa town (94%) [12], in South Ethiopia at Hawassa Referral Hospital (96%) [16], Southern Ethiopia (100%) [17] and Northern Tanzania (98%) [18]. The possible reasons for increment in prior studies might be using of health institution based study [10,12,[16][17][18] since pregnant mothers having positive attitude and better awareness may visit health institution and tested for HIV and in studies [10,12,16,17] the study participants were living in town thus they can easily access the information about VHCT and health services for test.…”
Section: Discussionsupporting
confidence: 91%
“…Similar study study done in Dominican Republic Vietnam indicates that 90% of pregnant mothers have been disclosed and suggest HIV testing and counselling to their male partner [19,20]. …”
Section: Discussionmentioning
confidence: 71%
“…Previous data show the perceived need to obtain a partner’s permission to be tested as a barrier to testing. 17 A previous study in Cambodia investigated the influence of partner participation in informational PMTCT classes on VCCT. 18 During the first visit to ANC, all women were invited to a class where information on PMTCT was provided.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who receive ANC outside Phnom Penh have less chance of undergoing HIV testing than mothers who receive ANC in Phnom Penh. 17 …”
Section: Introductionmentioning
confidence: 99%